X-ray Absorption Studies of the Catholyte LayerComponents in Thermal Batteries - H. HUSSEIN, FALAH; N. ALKHATEEB, AHMED; D. OMRAN, KAREEM; M. SARHAN, WALEED (Asian Journal of Chemistry, 2010)
Investigation of the X-ray diffraction values, for the catholyte components of the foreign cell and the linear spectrum for the diffraction values of these components, has been performed. Six obvious peaks appertaining to KCI, CaCrO4 and LiCl have been recorded demonstrating that these compounds are the main components of the DEB layer. No peak for the binder has been identified due to its very low concentration, which did not exceed 5%. In addition, a similar study was accomplished for the assembled cell, before running the thermal cell, via the definition of the peaks appertaining to the catholyte components and the amplitudes d-values. The peaks for the compounds used in the preparation of the catholyte layer, that is, KCI, CaCrO4 and LiCl have appeared. However, no peak was observed for the binder due to its low concentration. Furthermore, a comparison for the X-ray diffraction values and the linear spectrum for this diffraction for the catholyte layer of the assembled thermal cell, at different temperatures, namely, 400, 460 and 600°C; has been carried out At 400°C the findings revealed that this layer contained the compounds KCl, CaCrO4 and the alloy, CaLi2. Nonetheless, at 460°C, the results demonstrated that the layer consisted of the compounds KCI, CaCrO4, CaCl2 and the oxides mixture, Cr2O3·2CaO. However, the bands pertaining to CaLi2 and LiCl obtained at 400°C have disappeared indicating the reaction between Ca and Li ions to form the mentioned alloy, followed by the breakdown of this alloy with the release of electrons. Finally, at 600°C, the results confirm the existence of CaCrO4 and KCl besides the disappearance of the peaks belonging to CaCl2. In addition, a peak has emerged for LiO2, which was produced from the electrochemical reaction.